The Affinity to Execute Strategy Could Drive Firm Profitability. Is This True? What Role Does an Agile Leader Play? (Global Journal of Management and Business Research, 2022)
Purpose: Based on the assumption of the ADKAR theory and the dynamic capability theory, the interactions between strategy execution, agile leadership, and Deposit Money Banks (DMBs) firm profitability were examined. Methodology: Survey design was adopted, and a sample of 452 staff of eleven quoted DMBs in Lagos State, Nigeria, was the unit of analysis. PLS- SEM was used to test the study#x2019;s hypotheses. Findings: The results showed that strategy execution significantly impact DMBs profitability (Adj R 2 =0.373, p=0.000, Q 2 = 0.183). Supplementary test posited that agile leadership is a significant moderating variable given its ability to enhance the functional relationship between strategy execution and firm profitability of the DMBs in Lagos State, Nigeria (#x3B2; =0.160; plt; 0.050, Q 2 =0.198). Implications: The study, through its findings, established that strategy execution enhance firm profitability when manager exhibit agile leadership orientation. Thus, the DMBs should ensure that it looks into formulating strategies and identifying critical factors that can aid its successful implementation. It is equally critical for the management of the DMBs examined to imbibe the agile leadership orientation because such a leadership attribute potentially aid firm profitability. Originality: This study offers significant contribution to strategy execution literature within DMBs context in Lagos State, Nigeria. More so, add to scant empirical submission about the relevance of strategy execution and agile leadership.
Keywords: strategy execution; agile leadership; firm profitability; dynamic capability theory; ADKAR theory